2019
DOI: 10.1101/670893
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NMDA receptor in vasopressin 1b neurons is not required for short-term social memory, object memory or aggression

Abstract: The vasopressin 1b receptor (Avpr1b) plays an important role in social behaviors including aggression, social learning and memory. Genetic removal of Avpr1b from mouse models results in deficits in aggression and short-term social recognition in adults. Avpr1b gene expression is highly enriched in the pyramidal neurons of the hippocampal cornu ammonis 2 (CA2) region. Activity of the hippocampal CA2 has been shown to be required for normal short-term social recognition and aggressive behaviors. Vasopressin acts… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…We validated colocalization of Oxtr and Avpr1b transcripts in the CA2, with Oxtr extending into adjacent CA3 (Fig. 1a), consistent with previous reports 5, 23 . We also confirmed the reduction of Oxtr expression in the CA2 of HE and DKO mice and of Avpr1b expression in the DKO mice (Fig.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…We validated colocalization of Oxtr and Avpr1b transcripts in the CA2, with Oxtr extending into adjacent CA3 (Fig. 1a), consistent with previous reports 5, 23 . We also confirmed the reduction of Oxtr expression in the CA2 of HE and DKO mice and of Avpr1b expression in the DKO mice (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Restricted removal of both receptors from the pyramidal neurons of CA2 allowed us to investigate the functional significance of the cross-talk in this region. Previously, we showed that the life-long absence of Avpr1b resulted in impaired social recognition in both our knockout 6 and knockin 5 lines. We predicted similar, if not greater, impairments with the removal of both Oxtr and Avpr1b.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The mouse brain sample was prepared using the iDISCO+ procedure 21 , followed by immunolabelling with Alexa Fluor 555-conjugated secondary antibody against anti-tdTomato primary antibody. The entire brain volume after dual-view reconstruction spanned 10280 × 5160 × 1400 voxels (corresponding to 4 × 2 × 0.5 mm 3 , 138.3 GB in 16-bit format) 22 . We trained on 12 randomly selected subvolumes of single-view data to predict the dual-view joint deconvolved results, each comprising 128 × 128 × 128 voxels, then applied the model to a held-out, larger scale subvolume from the same dataset spanning 1184 × 1184 × 1218 voxels.…”
Section: Resultsmentioning
confidence: 99%